Urgensi Penerapan Minimalisasi Data dalam Upaya Pencegahan Penyalahgunaan Data Pribadi Nasabah di Sektor Perbankan Berdasarkan Undang-Undang Pelindungan Data Pribadi - Wishnu Angga Yudha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of the banking sector has led to an increase in the processing of customers' personal data, which can pose a risk of data misuse. One of the efforts to prevent this is the implementation of data minimisation, which emphasises that the personal data collected must be relevant, limited, and consistent with the legitimate purposes of processing, as well as transparent in accordance with the provisions of Article 27 of Law No. 27 of 2022 on Personal Data Protection (PDP Law). This study employs a normative legal analysis method with a descriptive-analytical approach, incorporating transformative legal theory and privacy rights protection to examine the application of the data minimisation by banks. The findings indicate that excessive data collection practices still frequently occur and may violate customers' privacy rights. Therefore, banks are required to disclose the types and relevance of customer data, conduct regular mapping and evaluation of the data required, and implement selective and secure information technology systems. This implementation constitutes banks' compliance with data protection principles, particularly security and accountability. Additionally, active customer involvement and oversight by authorities are crucial factors in ensuring the effectiveness of data minimisation implementation in the banking sector.